2019
DOI: 10.1038/s41598-019-39633-0
|View full text |Cite
|
Sign up to set email alerts
|

Allele specific chromatin signals, 3D interactions, and motif predictions for immune and B cell related diseases

Abstract: Several Genome Wide Association Studies (GWAS) have reported variants associated to immune diseases. However, the identified variants are rarely the drivers of the associations and the molecular mechanisms behind the genetic contributions remain poorly understood. ChIP-seq data for TFs and histone modifications provide snapshots of protein-DNA interactions allowing the identification of heterozygous SNPs showing significant allele specific signals (AS-SNPs). AS-SNPs can change a TF binding site resulting in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Our method is developed based on the established strategy for conducting allele-specific analysis on many types of sequencing data, which specifically focus on the sequencing reads on heterozygous loci. This includes allele-specific gene expression ( Zhang et al, 2014 ; Castel et al, 2015 ), allele-specific alternative splicing analysis ( Nembaware et al, 2008 ; Li et al, 2012 ), allele-specific binding of ChIP-seq ( de Santiago et al, 2017 ) and CLIP-seq data analysis ( Yang et al, 2019 ), allele-specific chromatin interaction ( Cavalli et al, 2019 ), and allele-specific chromatin accessibility ( Harvey et al, 2014 ; Zhang et al, 2019 ). To our knowledge, our method is the first to analyze allele-specific footprint.…”
Section: Discussionmentioning
confidence: 99%
“…Our method is developed based on the established strategy for conducting allele-specific analysis on many types of sequencing data, which specifically focus on the sequencing reads on heterozygous loci. This includes allele-specific gene expression ( Zhang et al, 2014 ; Castel et al, 2015 ), allele-specific alternative splicing analysis ( Nembaware et al, 2008 ; Li et al, 2012 ), allele-specific binding of ChIP-seq ( de Santiago et al, 2017 ) and CLIP-seq data analysis ( Yang et al, 2019 ), allele-specific chromatin interaction ( Cavalli et al, 2019 ), and allele-specific chromatin accessibility ( Harvey et al, 2014 ; Zhang et al, 2019 ). To our knowledge, our method is the first to analyze allele-specific footprint.…”
Section: Discussionmentioning
confidence: 99%
“…The allele-specific signals were also searched for in the ChIP-seq data for histone modifications in a study aimed to identify the regulatory variants involved in the development mechanisms of immune and B-cell related diseases [ 175 ]. The SNPs with allele-specific behavior in the available ChIP-seq datasets produced for the histone modifications defining promoters (H3K4me3) and enhancers (H3K4me1 and H3K27ac) and for domain boundary proteins (CTCF and SA.1) were the focus of this study.…”
Section: Rsnps On a Genome-wide Scalementioning
confidence: 99%
“…In support of genetic variation at enhancers influencing transcriptional regulation, Yu et al used HiC data to demonstrate that eQTLs tend to be in close spatial proximity with their target genes [157]. Additionally, by integrating the information of GWAS SNPs, TF binding site prediction and Hi-C/CHi-C data, studies have shown that non-coding SNPs can affect the binding of TFs, and can further potentially affect multiple target genes via 3D interactions [158,159].…”
Section: Functional Interaction Identification Via Omics-based Data Imentioning
confidence: 99%